Distinguished Approach of Qur’aic Invocation - Khan, Musaddiq Majid (Sheikh Zayed Islamic Centre, University of the Punjab, Quaid-i-Azam Campus (New Campus), Lahore-54590, Pakistan., 2016)
According to the Quran the man has been created by the almighty in his natural state. He turns to his lord, asks His shelter, seeks His protection. He has been formalized in acquaintance to the creator of that nature. He has been directed to face steadily and truly to the faith, establish Allah.s handiwork according to the nature on which He has made mankind.(1) As per the Quranic perspective all human being has accepted the covenant of the almighty and that is called in the Quran the natural state. It happened when Almighty the creator drew forth from the Children of Adam - from their loins - their descendants, and made them testify concerning themselves, (Saying): "Am I not your Lord (Who cherishes and sustains you)?"- They said: "Yea! we do testify!" (This), lest they should say on the Day of Judgment: "of this we were never mindful". (2)Whenever man starts deviating from that natural state the almighty reminds him about this covenant by dint of blooming affection and emotions, So that the man may awake his feelings with regard to the religious matters, such as Allah is the one and only. He alone is the worthy of worship including matters coming from that notion. The objective of these reminders are to clean that natural state which gets covered by the many issues we are facing in our lives, such as the family concerns, sociological problems, civilizational issues, customs, superstitions, fantasies of the world, temptations of the evil, lusts and self-advantages which drops him, the man, in the deep and dark well, and misguides him from that natural state to the infrequent state.